The Kephalaia of the Teacher : The Edited Coptic Manichaean Texts in Translation with Commentary - Gardner, Iain, (Nag Hammadi and Manichaean Studies ;, 1995)
The Kephalaia of the Teacher is the most detailed account available to modern scholarship of the teachings of Mani, and of the universal religion that he founded as the final successor to Buddha, Zarathushtra and Jesus. This volume provides the first complete English translation of the Coptic text (c. 400 CE), together with introduction, commentaries and indices. Topics include the apostleship of Mani, the practices of the Manichaean community, accounts of the heavenly and demonic beings and worlds, as well as discussions of astrology and religious psychology. In Manichaeism many of the gnostic and dualistic themes of early Christianity achieved the status of a world religion, and the subject is the heir to contemporary interest in heterodoxy and the deconstruction of received histories (see the Nag Hammadi codices).